Bacterial Shedding in Household Contacts of Cholera Patients in Dhaka, Bangladesh - Weil, Ana A. (The American Society of Tropical Medicine and Hygiene, 2014)
Multiple Vibrio cholerae infections within the same household are common. Household contacts of patients with cholera were observed with daily clinical assessments and collection of rectal swab cultures for nine days after presentation of the index case. During the follow-up period, 71 (24%) of 294 household contacts developed a positive V. cholerae rectal swab, signifying bacterial shedding. The average length of bacterial shedding was 2.0 days (95% confidence interval 1.7–2.4). However, 16 (5%) of 294 contacts shed V. cholerae for ≥ 4 days. In a multivariate analysis, malnutrition was predictive of long-term shedding (odds ratio = 1.4, 95% confidence interval = 1.3–13, P = 0.02). High rates of V. cholerae infection and bacterial shedding among household contacts of cholera patients represent an opportunity for intervention to reduce V. cholerae transmission.